Integrating Rough-and-Tumble Play in Martial Arts: A Practitioner’s Model - Blomqvist Mickelsson, Tony; Stylin, Pilo (Frontiers in Psychology, 2021)
This paper introduces a model that explain psychosocial development by embedding the developmental concept of rough-and-tumble play (RTP) into the contextual settings of martial arts (MA). Current sport-for-change literature relies on theories that address contextual factors surrounding sport but agrees that sport in itself does not facilitate developmental outcomes. In contemporary time where Western societies invest substantial resources into sport programs for its psychosocial contribution, this becomes problematic. If the contextual factors surrounding sport are exclusively what produces developmental outcomes, what is the rationale for investing resources into sport specifically? We challenge this idea, and argue that, although contextual factors are important to any social phenomena, the developmental outcomes due to sport can also be traced to the corporeal domain in sport. To date, we have lacked the theoretical lenses to articulate this. The developmental concept of RTP emphasizes how ‘play fighting’ between consenting parts stimulates psychosocial growth, in through its demand for self-regulation and control when ‘play fighting’ with peers. In short, RTP demands individuals to maintain a self-regulated mode of fighting and is contingent on a give-and-take relationship to maintain the enjoyment. RTP can thus foster empathy and pro-social behavior and has strong social bonding implications. However, such play can also escalate. A fitting setting to view as moderated RTP is MA, because of its resemblance to RTP but also because of its inherent philosophical features, which emphasizes self-regulation, empathy, and pro-social behavior. This paper outlines what constitutes high-quality RTP in a MA context and how this relates to developmental outcomes. By doing so, we present a practitioner’s framework in which practitioners, social workers and physical educators can explain how MA, and not merely contextual factors, contribute towards developmental outcomes. In a time where sport is becoming increasingly politicized and used as a social intervention, it too becomes imperative to account for why sport, and in this case MA, is suitable to such ends.